N6-Methyladenosine RNA Methylation Regulator-Related Alternative Splicing (AS) Gene Signature Predicts Non–Small Cell Lung Cancer Prognosis - Zhao, Zhenyu; Cai, Qidong; Zhang, Pengfei; He, Boxue; Peng, Xiong; Tu, Guangxu; Peng, Weilin; Wang, Li; Yu, Fenglei; Wang, Xiang (Frontiers in Molecular Biosciences, 2021)
This research was an aim to explore the alternative splicing (AS) events that were associated with N6‐methyladenosine (m6A) RNA methylation regulatory genes and served as prognostic biomarkers in non-small cell lung carcinoma (NSCLC). Alternative Splicing data is obtained from the TCGA database. According to the current study, we obtained 13 m6A regulatory genes and expression data from the TCGA database. We used Univariate Cox regression analyses to select the differential expression genes (DEGs) associated with the survival status. Two m6A regulatory DEGs were found associated with LUAD and LUSC overall survival (OS) respectively. Then, through the WGCNA analysis method select AS events and construct the AS signature. There were 1103 and 321 AS events associated with the two m6A regulatory DEGs in LUAD and LUSC respectively. Through Univariate Cox regression analyses, Lasso Cox regression analyses, and multivariate Cox regression analyses, only seven AS events to construct the prognostic signature, respectively. The area under the curve (AUC) of receiver operating characteristic (ROC) for the AS prognostic signature of the LUAD and LUSC showed good sensitivity and specificity in five years. The network of the m6A regulatory DEGs and AS events may suggest the working mechanism in NSCLC. Additionally, the performance of the nomogram incorporating AS signature was evaluated by the calibration cures and ROC curves.